Rancang Bangun Aplikasi Pemesanan Paket Tour And Travel Berbasis Web (Studi Kasus : CV. Yukkita Tour And Travel Rantauprapat) - Sari, Ayu Widya (Journal of Computer Science and Information System(JCoInS), 2022)
Cv Yukkita Tour And Travel is a company engaged in the service of tour package destinations. In running its business, it still uses a manual system. When ordering a tour package, the customer must come to the Cv Yukkita Tour And Travel office or by telephone. For data storage customer orders have not used a database. By building a web-based tour and travel application on CV Yukkita Tour And Travel, it can make it easier for customers to order tour packages and quickly receive information about tour packages. Implementation of the program using the php programming language and mysql database. The results of the study are in the form of a web-based tour and travel application that can facilitate booking tour packages.